MODELING LEARNING GAME BASED DIGITAL TO CHILDREN OF SENIOR HIGH SCHOOL FOR GEOGRAPHY SCIENCE BASED ON UNITY - Astrid Novita Putri; Wiratama Adi Wibawa (Jurnal Informatika Upgris, 2016)
The development of information and communication technology is now a major effect on manyaspects of life, even human behavior and activities are now a lot depends on the information andcommunication technology. One example is the use of technology in teaching and learning, namely withthe game. The game is already familiar to the students. When students are lazy to read books whilestudying, they are cool to play games. Therefore, the author makes an effective solution in learning sothat they are not lazy to study. This game was designed with the concept of 2D so it can be run onsmartphones that have lower specs. To build this game, the author uses Unity 3D 5.4. So, students canlearn with pleasure and do not get bored while studying.